PALAEOENVIRONMENTAL CONSIDERATIONS ABOUT THE ITARARÉ SUBGROUP AT ARAÇOIABA DA SERRA, STATE OF SÁO PAULO (UPPER CARBONIFEROUS, PARANÁ BASIN), BRAZIL (Ameghiniana, 2014)
Detailed qualitative and quantitative palynological analyses of cores from the Geomater well (A-IG-85) and samples from four outcrops along the Raposo Tavares highway (SP-270) at km 118.6, 122.7, 123.7, and 125.8, Aracoiaba da Serra, State of Silo Paulo, Brazil, revealed a highly diversified microflora of pteridophyte spores and gymnosperm pollen grains which have led to new ideas about the age and geological evolution of the Itararé Subgroup in the northeastem Paraná Basin. The species Deusilites tenuistriatus Gutiérrez, Césari and Archangelsky, is found throughout most of the studied section (about 2 12m thick) of mainly claystones, siltstones and rhythmites, as well as in the studied outcrops composed of sandstones, siltstones and diamictites. This species is found in Lower Permian strata of the Chacoparanense Basin of Argentina and in the Paraná Basin of Southem Brazil. Its occurrence in Aracoiaba da Serra, whose Late Carboniferous age is based on sporomorphs, extends its range from this age to the Early Permian. Palaeoenvironmental considerations are put forth.